Research on SiC Speed Controller for High-Voltage Distributed Electric Propulsion System - Labin Wang; Yunhan He; Yun Xu; Li Fan; Junhua Xiang (International Journal of Aerospace Engineering)
The shift towards green aviation necessitates the adoption of all-electric aircraft, marking an essential trend in the aviation industry. Distributed propulsion systems enhance aircraft flexibility and reliability, synchronously reducing performance demands and costs of single propulsion units compared to centralized propulsion system. The high reliability and lightweight characteristics of brushless DC motors have made them increasingly popular in distributed propulsion systems. Despite its advantage which helps to build efficient aircraft aerodynamic layout, there are more cables in the distributed propulsion system, which accounts for most of the weight of the aircraft. To address this, all-electric aircraft utilizes high-voltage power supply to reduce the current, so it uses SiC MOSFETs as power devices to improve its efficiency and heat dissipation. The speed controller in all-electric aircraft determines the efficiency and reliability of the propulsion unit. However, the traditional high-voltage speed controller poses challenges for aircraft maintenance because of high cost. Therefore, this paper emphasizes the significance of designing a low-cost, high-performance speed controller for all-electric aircraft. Challenges such as circuit interference, battery voltage fluctuation, and sampling noise affecting the high-voltage controller during operation are solved, respectively. First, to address the likelihood of mutual interference in the bridge arm, a self-bootstrapping voltage reduction drive mode is designed to turn off SiC MOSFET and enhance circuit anti-interference. Second, to solve the challenge of wide battery voltage fluctuation range and inconsistent controller output, an adaptive pulse width modulation (PWM) regulation mode for battery voltage is proposed, ensuring stable controller output. Finally, to counteract the impact of the comparator threshold on zero-crossing sampling, an electrical angle delay method based on delay compensation is designed to improve the efficiency of the brushless DC motor during operation. Experimental results show that the three solutions proposed in this paper are helpful to improve the anti-interference, stability, and efficiency of the controller in the high-voltage distributed electric propulsion system and contribute to reduce the cost and weight in the propulsion unit.